Analysis of the Effect of Dimensions of Fraud Diamond on Fraud Behavior of Students of Accounting University Semarang" - Wanson Kornelius Manik; Ngurah Panji Mertha Agung Durya (Journal Markcount Finance, 2024)
This study aims to determine the effect of the fraud diamond dimension on the fraud behavior of accounting students at the University of Semarang. Cheating is a fraudulent act committed by someone to gain profit for himself by taking advantage of other people. The data analysis technique in this study was multiple linear regression analysis using data from Semarang University accounting student respondents in the 2019 and 2020 classes. The results showed that pressure had an effect on academic cheating, while opportunity, rationalization and ability had no effect on academic cheating. The results of the model feasibility test show that pressure, opportunity, rationalization and ability simultaneously influence the academic fraud of accounting students at the University of Semarang.